2018
DOI: 10.1590/1806-9282.64.10.888
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oxidative damage and enzymatic antioxidant system activity on the umbilical cord blood and saliva from preterm newborns with risk factors for early-onset neonatal sepsis

Abstract: SUMMARY BACKGROUND: To determine the concentration of the Lipid Peroxidation Marker: Malondialdehyde (MDA), and Antioxidant Markers: Superoxide Dismutase (SOD), Glutathione Peroxidase (GPX), Catalase (CAL) in umbilical cord blood and in unstimulated saliva in the first 24 and 48 hours of life in the PTNB of mothers with and without risk factors for early-onset neonatal sepsis. METHODS: Cross-sectional study with the signing of informed consent by the pregnant women and application of a standard questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…Under physiological conditions, this is counteracted by a concomitant rise in antioxidants. However, if this rise does not take place, excess ROS leads to oxidative damage, as observed in mothers with pregnancies complicated with obesity or diabetes [22][23][24]. Our study did not reveal changes in maternal plasma oxidative stress markers, and there was an elevation in catalase enzyme activity.…”
Section: Discussionmentioning
confidence: 41%
“…Under physiological conditions, this is counteracted by a concomitant rise in antioxidants. However, if this rise does not take place, excess ROS leads to oxidative damage, as observed in mothers with pregnancies complicated with obesity or diabetes [22][23][24]. Our study did not reveal changes in maternal plasma oxidative stress markers, and there was an elevation in catalase enzyme activity.…”
Section: Discussionmentioning
confidence: 41%
“…The studies that reported a positive association between oxidative stress and/or development of diseases related to prematurity were 72.2% (n = 13); 27.7% (n = 5) showed no significant association. Positive correlations were found in IUGR; 8 , 13 , 25 NEC; 10 , 20 morbidity and mortality; 5 , 26 BPD, IVH; 10 FIRS; 21 early-onset neonatal sepsis; 22 RDS 12 and ROP. 27 CLD, 19 DNA damage, 4 IVH, 24 cardiac functions, 23 and endothelial dysfunction 9 were not associated with oxidative stress levels in included studies.…”
Section: Resultsmentioning
confidence: 92%
“…Synthesis of the articles, year of publication, type of study, sample, source of specimen, biomarkers, diseases evaluated, and the main outcomes are described in Table 1 . 3 , 4 , 5 , 8 , 9 , 10 , 12 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28
Figure 1 Flowchart of the study selection process for the integrative review on oxidative stress in premature newborns.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During labor, a newborn changes the environment from intrauterine to extrauterine, and at the same time, partial oxygen pressure in newborn's arterial blood rises rapidly from 25 mmHg to 100 mmHg. As a result of hyperoxia, a significant amount of free radicals is generated [ 77 , 78 ]. Among procedures which are common in neonatal intensive care units (NICU), oxygen therapy [ 79 ] and parenteral nutrition [ 80 ] markedly promoted oxidative damage.…”
Section: Neonatal Diseases Related To Ros and Intense Inflammationmentioning
confidence: 99%